Harmonic Tidal Analysis of Long Time Series - Foreman, M G. G.; Neufeld, E. T. (The International Hydrographic Review, 2015)
A harmonic tided analysis program is developed for observational records of 18.61 years or longer. The amplitudes and phases of over five hundred astronomical and shallow water constituents are calculated using a least squares approach. The program is tested with 38 years of hourly observations at Victoria and the amplitudes and phases of satellite constituents whose amplitudes lie above the background noise level are generally found to be consistent with potential theory. Predictions based on the results of a 19-year analysis are found to be only slightly better than those based on averages from 19 one-year analyses, thereby confirming the accuracy of G odin’s [1972] satellite correction algorithm and satellite inference based on potential theory relationships. However it is demonstrated with constituents NO1, J1, N2, and L2, that results from the 38-year analysis can be used to improve the satellite inference calculations in shorter analyses. Based on the stability of the 38 one-year analyses, recommendations are also made for the inclusion of additional constituents in the standard prediction of tides at Victoria.